Developing talent for organizational results training tools from the best in the field - Biech, Elaine; ProQuest (Firm) (San Francisco : Pfeiffer, 2012)
"While a single training company is often the provider for a client specific solutions, the combination of innovative approaches uncovered through the exchange of the collective experience of many providers/training suppliers creates a powerful arsenal of tools. These tools make a difference in the success of corporate enterprise-wide performance. ISA (The Association of Learning Providers) is the trusted network that brings suppliers together to share and debate the art and science of innovative learning and performance for work-related, enterprise-wide people performance on the job. This volume brings together ISA members to tell their story of what really works through a variety of activities, instruments, and articles"--
section 1. Communicating to succeed -- section 2. Moving into management -- section 3. Executive essentials -- section 4. Developing leaders -- section 5. Shaping a vital culture -- section 6. Invigorating your training process for results -- section 7. Timely training techniques -- section 8. Focus on individual development -- section 9. Caring customer service and sales.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Employees -- Training of; Organizational change; Personnel management; Electronic books